Assessment of Marine Ecotourism Development Potential in Lapin Beach, North Rupat, Riau Province - Akbar, Aidil Rahmad; Samiaji, Joko; Yoswaty, Dessy (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Lapin Beach in North Rupat, Riau Province, has excellent potential to be developed as a marine ecotourism area due to its natural beauty and local cultural richness. However, no scientific research has explored this potential in depth. This study aims to analyze the potential and formulate strategies for the sustainable development of marine ecotourism in Lapin Beach to improve the welfare of local communities. The research was conducted from December 2024 to February 2025. Data were collected through observation, interviews, questionnaires, and water quality measurements. The analysis used is the coastal tourism suitability index and the SWOT approach. The results showed that Lapin Beach has strong potential for ecotourism, supported by easy access, natural panoramas, and community participation. The tourism suitability index ranged from 83.97 to 86.53%, indicating a high suitability (S1). Water quality and coastal topography support tourism activities. SWOT analysis suggested strategies including promotion, facility improvements, and community engagement in maintaining sustainability. Recommended development strategies include optimizing natural attractions, empowering local businesses, improving infrastructure, and enhancing monitoring efforts. Further studies should consist of aspects of biota, vegetation, and economic impact to support sustainable ecotourism management and enhance community well-being.